(untitled) (Research, Society and Development, 2025)
The study aimed to describe the knowledge and practices of caregivers of hospitalized patients regarding contact precaution measures, discussing their contribution to adherence to institutional safety protocols and identifying elements for the development of educational materials. This is a social and qualitative study based on the Convergent Care Research (CCR) approach, conducted between June and November 2024 in a federal teaching hospital in Rio de Janeiro, Brazil. Data were collected through semi-structured interviews with ten caregivers and analyzed using thematic content analysis. The results revealed a female predominance among participants and limited understanding of microorganisms and infection prevention measures. Institutional communication weaknesses, lack of systematic guidance, and gaps in comprehension of contact precautions were identified. Participants suggested the use of accessible educational tools, such as posters and illustrated brochures, to reinforce instructions. It is concluded that the active participation of caregivers is essential for patient safety, requiring strengthened educational strategies and effective communication between the healthcare team and families. The implementation of standardized protocols and didactic materials that promote engagement and shared responsibility in safe care is recommended.